Introduction to Issue Seventeen - Laurie Moberg, Managing Editor (Open Rivers, 2020)

(untitled)
In recent years, the practice of land acknowledgements—making statements to acknowledge that white settlers to Turtle Island (what we now know as North America) are all on lands unethically, unconscionably, taken from Indigenous peoples who lived and thrived here long before settlers—has become common.